The effect of synoptic patterns on pressure level (500 Hectobascal) on the occurrence of heavy rains in Sulaymaniyah province - ali, othman abdulrhman; ali, ahmed taha (Al-Adab Journal, 2020)
Heavy rain refers to the large number of rains in a specific period of time, and because of the different geographical characteristics, the determination of the ingredients and quantities of these rains varies from one region to another. Because of the topography and the geographical location of the Sulaymaniyah Governorate, which is located in the semi-tropical regions, therefore heavy rain falls, including heavy rains, therefore the presence of rugged mountains in this province has a great importance in reserving air humidity and thus heavy rains fall. In this paper, the classification of synoptic patterns of heavy rains in Sulaymaniyah Governorate and the climatic characteristics of this phenomenon have been highlighted according to location and time.The research indicates that the occurrence of heavy rains occurs in mountainous regions more than the plain areas, and for the time of the occurrence of the phenomenon there was a difference in the frequency of heavy rains according to the seasons for all stations in the winter (61.4%) and (20.5%) in the spring and ( 17.9%) in the fall semester. In addition, at the level of months, months came (February, December, January), as the most frequent numbers of heavy rains were recorded. As for the classification of synoptic patterns, and after determining (97) joint days for heavy rains in the Sulaymaniyah governorate and their representation with synoptic maps, the maps were distributed to (7) different groups. The most frequent group (D) was (45) members, meaning the eastern Mediterranean dawn.